Neuro-Ophthalmology Illustrated - Biousse, Valérie (Thieme Medical Publishers, Incorporated, 2019)
A highly praised, well written, and richly illustrated modern classic in neuro-ophthalmology now in an exciting new edition with video clips! Neuro-ophthalmology is an ""overlap"" specialty, encompassing all disorders that affect the parts of the central nervous system related to vision. Neuro-Ophthalmology Illustrated, Third Edition by world-renowned neuro-ophthalmologists and professors Valérie Biousse and Nancy J. Newman expands on the widely acclaimed prior editions, lauded with awards by the Association of American Publishers and the British Medical Association. The updated text reflects.